Uncovering educator perspectives of occupation‐centred education in Australia: A qualitative study. (28th September 2018) - Di Tommaso, Amelia; Wicks, Alison; Scarvell, Jennie; Isbel, Stephen
Abstract : Background/aim: Occupation and an occupational perspective of health and wellbeing are required to be taught in accredited occupational therapy programmes internationally. Current research into occupational therapy education has commonly focused on curriculum design and the experience of students and their developing skills for practice. Little research has focused on the perspectives of educators and in particular their own reflections and beliefs on the use of occupation in occupational therapy education. The aim of this study was to uncover Australian educator perspectives of occupation in occupational therapy education. Method: This study utilised a qualitative research framework. Eight occupational therapy educators and practice education coordinators completed semi‐structured interviews. Educators ranged in experience from two to over 20 years in the university sector. The interview transcripts were transcribed verbatim, forming the data for analysis. Braun and Clarke's thematic analysis was used to analyse the dataset. Results: Three themes emerged from the data: occupation is our framework; the balance between practice education and occupation‐centred education; and educators changing the focus. Overall, educators believed that the 'occupation for health' philosophy and its application are important foundations for education. However, educators provided varied responses on how to teach these concepts to students. Conclusion: Gaining educators' opinions on the importance of occupation in education is beneficial for ensuring consistency throughout occupational therapy curricula. Theoretical models were endorsed by educators to foster occupation‐based practice. Educators must continue to innovate within the profession for occupation‐based approaches in practice and education to be strengthened in the future.